A human behavior model of multi-agent attention based on actor–observer switching for asynchronous motion tasks with limited field of view. (3rd July 2019) - Zhang-Xu, Tingting; Kühnlenz, Kolja
Abstract : This paper presents an overt visual attention approach for multi-agent systems and asynchronous motion tasks with limited field of view based on human behavior. In a first step, results from a study on human temporal attention switching during a formation task are presented. Three temporally switching human behaviors (observer, actor, idler) are identified and characterized towards distributions of attention foci. In a second step, based on these results, a behavior switching attention strategy is proposed. The strategy is evaluated in simulations of various formation task scenarios illustrating the effectiveness of the approach. GRAPHICAL ABSTRACT: